Integration of Traffic Knowledge in the PPKN Learning Process at SMK 7 Bone - Ariska; Mustari; Najamuddin (DIROSAT: Journal of Education, Social Sciences & Humanities, 2023)
The aim of this research is to find out about (i) The integration of traffic knowledge in the PPKn learning process at SMK Negeri 7 Bone, (ii) The level of compliance with traffic laws for students at SMK Negeri 7 Bone, (iii) The strategies implemented by the school and the police in integrating traffic knowledge for students. This type of research is mixed methods, namely a type of research that combines qualitative and quantitative research using percentage analysis. The results of the research show that, (i) Integration of traffic knowledge in the PPKn learning process at SMK Negeri 7 Bone is found in several basic competencies in classes XI and ii) The level of traffic knowledge for students is still relatively low, this can be seen from the traffic education knowledge indicator (iii) The strategy that the school has implemented in integrating traffic knowledge through several activity and outreach programs delivered directly by the Principal and the police